INSENTIF DAN IMPLIKASINYA PADA KINERJA GURU DALAM PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH DASAR - Waspodo Tjipto Subroto, (Pendidikan Dasar, 2010)
Abstract; This study focuses on the influence of the incentives given to Elementary school teachers on their performance and the education quality. The sample is 186 teachers taken from 935 schools comprising 12394 teachers. By applying structural equation modelling analysis, the findings are: 1) the amount of teachers pay and the subsidies from the central and regional governments and the school committee influence the teacher performance and the education quality; 2) the honorarium has impact on the teacher performance; 3) the teacher performance influences the education quality indicated by the quality of values and quantity of study.